Maternal Factors and Perinatal Outcome of Preterm Birth: A Prospective Study - Zalak V. Karena (New Horizons in Medicine and Medical Research Vol. 11, 2022)
The aim of this study is to analyse the distribution of risk factors of preterm birth in tertiary centre of Gujarat and the burden as well as outcome of preterm births in the institute. The proportion of preterm birth amongst advanced maternal age women is significantly higher than adult aged women. In the research, 100 women experiencing preterm labor or a preterm termination of pregnancy were enrolled. They were assessed by a medical history, physical examination, and ultrasound. All of the patients were given corticosteroids. The researchers looked at maternal risk factors, obstetric outcomes, and perinatal outcomes up to discharge. Preterm birth can be prevented, checked for, and treated by specialized antenatal programs for anemia, malnutrition, infection, and high-order pregnancy.